Mechanical and Electroconductive Properties of Mono- and Bilayer Graphene–Carbon Nanotube Films - Michael M. Slepchenkov (Coatings, 2019)
This article presents the results of a computer study of electrical conductivity and deformation behavior of new graphene⁻carbon nanotube (CNT) composite films under bending and stretching. Mono- and bilayer hybrid structures with CNTs (10,0) and (12,0) and an inter-tube distance of 10 and 12 hexagons were considered. It is revealed that elastic deformation is characteristic for mono- and bilayer composite films both in bending and stretching. It is found that, in the case of bending in a direction perpendicular to CNTs, the composite film takes the form of an arc, and, in the case of bending in a direction along CNTs, the composite film exhibits behavior that is characteristic of a beam subjected to bending deformation as a result of exposure to vertical force at its free end. It is shown that mono- and bilayer composite films are more resistant to axial stretching in the direction perpendicular to CNTs. The bilayer composite films with an inter-tube distance of 12 hexagons demonstrate the greatest resistance to stretching in a direction perpendicular to CNTs. It is established that the CNT diameter and the inter-tube distance significantly affect the strength limits of composite films under axial stretching in a direction along CNTs. The composite films with CNT (10,0) and an inter-tube distance of 12 hexagons exhibit the highest resistance to stretching in a direction along CNTs. The calculated distribution of local stresses of the atomic network of deformed mono- and bilayer composite films showed that the maximum stresses fall on atoms forming covalent bonds between graphene and CNT, regardless of the CNT diameter and inter-tube distance. The destruction of covalent bonds occurs at the stress of ~1.8 GPa. It is revealed that the electrical resistance of mono- and bilayer composite films decreases with increasing bending. At the same time, the electrical resistance of a bilayer film is 1.5⁻2 times less than that of a monolayer film. The lowest electrical resistance is observed for composite films with a CNT (12,0) of metallic conductivity.